Thrice-weekly insulin injection with nurse's support for diabetic hemodialysis patients having difficulty with self injection - Shoji, Tetsuo; Emoto, Masanori; Mori, Katsuhito; Morioka, Tomoaki; Fukumoto, Shinya; Takahashi, Tatsuji; Matsumoto, Akihide; Nishizawa, Yoshiki; Inaba, Masaaki (Osaka City medical journal, 2012)
Although poor glycemic control is known as an independent predictor of mortality in diabetic hemodialysis patients, it is often difficult for some patients to perform standard self injection insulin therapy. Some practical methods are needed for such patients. We evaluated the usefulness of a new regimen of insulin therapy, namely thrice-weekly insulin injection with nurse's support (TWINS) using insulin NPH or glargine at the end of each hemodialysis sessions in 5 outpatients on hemodialysis with type 2 diabetes mellitus showing HbAlc levels > or = 8.0% (JDS). HbA1c levels were successfully decreased in all patients from 9.3 +/- 1.1% to 6.9 +/- 0.7% (mean +/- SD) in six months without hypoglycemia symptoms. These preliminary results suggest that this regimen can be one of the practical choices in poor-controlled diabetes patients on regular hemodialysis who have difficulty in self injection of insulin.